“Exploring the contribution of alternative food systems towards food security: a case study of the siyazenzela food garden project” - Mikosi, Khathutshelo (Department of Environmental and Geographical Science, 2020)
In South African urban centres the development of Alternative Food Systems (AFS) have been partially attributed with seeking to overcome the exclusion enforced through the apartheid regime’s racial planning policies. It was during this period that poor African households were forcibly relocated to the periphery of urban areas, creating even greater distances between themselves and everyday amenities, such as food retailers, which were typically found in more affluent zones. As a result, AFS emerged through informal activities to reduce the lack of access to necessary resources that these underserved communities experienced. Even at the end of the apartheid regime and the subsequent increased expansion of formal food retailers in many of these low-income communities, access to food continues to be major challenge. Consequently, AFS fulfil an essential role by providing low income neighbourhoods with alternative and affordable sources of food. This research examines the extent to which AFS, such as the Siyazenzela food garden project, contribute to food security for the Phiri community in Soweto and if it is feasible for the project to meet these needs single-handedly. The results indicate that the project plays an important role by providing locals with accessible, fresh, diverse, affordable and culturally acceptable foods. However, one of the considerable challenges for the initiative is its inability to maintain a constant supply of produce throughout the year. This leaves many of its patrons having to seek food from other sources, which may not necessarily offer the same quality and affordable goods, or they resort to consuming less fresh produce. Therefore, the study brings to the surface the need to question how such systems function and if their methods always result in safe, healthier and environmentally friendly grown produce as the literature assert.